Design of the Control Device for the Electrosurgical Generator - Alaq, Zahra Suhail; Hussein, Fatima Hayder; Rasool, Zahraa Muhammed; Abdulwahid, Noor AL-Huda Saad; Ali, Ahmed Ayad (American Journal of Botany and Bioengineering, 2025)
Electro surgery is a systematic process within different surgical procedures; The basic working idea was to heat the tissues in an area of focus using the radio-frequency high-power alternating current signals. As a result, several functionalities, including cutting, removal of tissues, and altering of blood flow across the damaged tissues, are achieved. In this work, sliding mode controller is used for regulation output power of the electrosurgical system to meet level which causes no effect on the patients. Sliding mode control one of the nonlinear controller which have many advantages such as Robustness against uncertainties and disturbances, simplicity of implementation, insensitivity to model inaccuracies, effective control of nonlinear systems, and strong stability guarantees. In this work, one case of the tissue impedance was assumed for the controller of the electrosurgical unit i.e. constant impedance. Sliding mode controller give well behavior for the power regulation. Matlab file is the software used for the simulation process.